2018
DOI: 10.1159/000489925
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of High-Risk Adenoma Occurrence at Surveillance Colonoscopy in Patients Who Undergo Colorectal Adenoma Removal

Abstract: Objectives: Surveillance colonoscopy is recommended after polypectomy because adenoma recurrence is common. The aim of this study was to evaluate the predictors of high-risk adenoma occurrence at surveillance colonoscopy in patients who undergo colorectal adenoma removal and to clarify the association between age and recurrent colorectal adenoma. Methods: This retrospective study included 563 patients who had colorectal adenomas at baseline colonoscopy and who underwent surveillance colonoscopy. The risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Potentially, a longer follow-up would increase the number of events in this category and a significant association would be found as expected. This factor is considered a main quality indicator for the colonoscopy procedure and was associated with subsequent CRC in other studies (Lieberman et al 2000;Amano et al 2018;Lee et al 2018). If no polyps were found, a risk for CRC remained.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, a longer follow-up would increase the number of events in this category and a significant association would be found as expected. This factor is considered a main quality indicator for the colonoscopy procedure and was associated with subsequent CRC in other studies (Lieberman et al 2000;Amano et al 2018;Lee et al 2018). If no polyps were found, a risk for CRC remained.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that colorectal adenomas exhibit an intriguing link with arterial stiffness, a well-known indicator of cardiovascular disease. [9][10][11][12][13] PWV is a direct indicator of arterial wall elasticity and the most traditional measure used to gauge the degree of vascular rigidity. On the other hand, it is dependent on the patient's blood pressure at the time of measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported the relationship between peripheral vascular diseases and colorectal adenomas using ABI and PWV. [9][10][11][12] Additionally, a recent study reported an association of arterial stiffness measured by PWV with the occurrence of high-risk adenomas and serrated lesions. 13 However, no studies have assessed the association between CAVI and adenoma risk.…”
Section: 8mentioning
confidence: 99%
“…Although no significant differences were found in the risks of metachronous CRC between the 1-2 NAAs and 3-4 NAAs groups and between the 3-4 NAAs and $5 NAAs groups, there was a tendency to increase the risk between the 1-2 NAAs and 3-4 NAAs groups. Although polyps were not found, the risk for metachronous CRC remained; moreover, a longer follow-up could increase the incidence of CRC, and the main quality indicators of colonoscopy were associated with metachronous CRC (29)(30)(31)(32). Our metaanalysis did not include only studies that performed a qualified colonoscopy.…”
Section: Review Articlementioning
confidence: 99%